P93 The hospice of St Francis spring centre: collaboratively reaching more people. (1st October 2013) - McLaughlin, Kimberley; Traxler, Polly; Valentine, Wendy
Abstract : Context: "Hospices will need to change is beyond doubt. The scale of the challenge ahead is dramatic and will require hospices to significantly increase the extent and scope of end of life services" (Calanzani et al 2013). Since 2007, cancer diagnoses have increased by 16% in Hertfordshire and over the next 10 years projected to rise a further 14%. This collaborative project with our neighbouring hospice provides a locality-wide community programme to support those recently diagnosed or living with serious illness, their families, carers, friends and the community. Over the next 3 years, The Spring Centre will reach over 1, 000 more patients and their families. Approach: Re-aligning existing resources and community engagement is key to our programme. The St Francis Choir, Coffee Mornings and Film Club engage our community in regular activities throughout the year. Medical, nursing and therapists clinics provide physical, emotional and psychological support. Focused groups by our rehabilitation team range from fatigue management workshops, breathlessness groups, complementary therapy, gardening and creative therapies. Our Carers programme offers individualised support including benefits advice and relaxation classes. A variety of groups for bereaved adults, children and young people invite opportunities to share experiences, enjoy our gardens and even cooking classes! Outcome measures used to identify the effectiveness of attending the pilot fatigue group in 2012 showed that 80% of people felt they had the skills and energy levels to participate in more social or work activities. Feedback also highlights benefits, 'the carers' support group is a lifeline to me'. Conclusion: The Spring Centre at The Hospice of St Francis is an example of thinking strategically and collaboratively about the role of our hospice, re-aligning existing resources and delivering the care that people want and need.